DUKUNGAN BPRS PADA IMPLEMENTASI JAMINAN PRODUK HALAL - Panglima Thariq Al Huda (Islamic Economics and finance in Focus, 2023)
BPRS is one of the financial institutions that has great potential to continue to grow. Challenges such as the threat of a global crisis require it to be more adaptive to the digitalization era. At the same time, BPRS also has a role as a partner of MSMEs that supports and is at the forefront of the revival and recovery of the national economy. Moreover, the government has a policy related to the obligation of products entering, circulating and trading in Indonesia to be halal certified. Seeing this opportunity, it is time for BPRS to take the initiative directly to provide services to MSMEs or grassroots so that they can implement halal product assurance in Indonesia. This research adopting a literature review. The results of the research are BPRS Buana Mitra Perwira as an intermediary institution by channeling financing as a form of equity participation to business actors in developing their business both to increase raw material capital and others. In addition, BPRS also established a halal center to assist its customers to produce halal-certified products. Through this assistance has a significant impact on MSMEs.